2018
DOI: 10.5539/ass.v14n10p21
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Beliefs as Mediator in the Relationship Between Activating Event and Stress in Malaysian Fully Residential School Teachers

Abstract: Teacher stress has been a major concern among researchers as it has negative impact on teaching profesion. This study aimed to test the mediating effect of irrational beliefs on the relationship between activating event as the independent variable and stress as the dependent variable. Data were collected from a sample of 201 teachers from seven Malaysian Fully Residential School (FRS) in the Johor state by using stratified random sampling. The Teacher Irrational Beliefs (TIB), Teacher Activating Event (TAE), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Psychological well-being or mental health among teachers has become an increasing issue in many countries [ 25 , 26 , 27 ]. Nevertheless, most studies in school settings have been on students rather than on the health and well-being of teachers [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological well-being or mental health among teachers has become an increasing issue in many countries [ 25 , 26 , 27 ]. Nevertheless, most studies in school settings have been on students rather than on the health and well-being of teachers [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Female teachers with heavy workloads in school or home were most likely to have poor mental health. Meanwhile, Ghani, Ahmad and Ibrahim [ 25 ] concluded that special education teachers suffered mild stress and indicated student misbehavior as the primary source of teacher stress, followed by workload, time and resources difficulties, recognition, and interpersonal relationships. A comparative study by Kavita and Hassan [ 23 ] on teachers in Selangor revealed that secondary school teachers, compared with primary school teachers, perceived more stress in all stress factors, which were rapport with parents and co-workers, workload, time constraints, student attitude, recognition and support, and lack of resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the higher the IB score, the greater the psychological distress, and results in decreased work efficiency or productivity. 26,29,30 Referring to Ellis, we understand that individuals can have erroneous ideas (destructive, unconscious beliefs, which result in maladaptive tendencies and cause psychological distress) that can be replaced with the correct or more adaptive ideas. 7,8,12 Compared to other countries, job demands of female workers in Bali are similar to India, which are traditional norms that add to the social obligations due to marriage, and women have greater domestic responsibilities than their spouses.…”
Section: B Amentioning
confidence: 99%
“…This can result from psychological distress experiences and related to the risk of being suffered from some illness among the person. The higher the IB results in easily on being decreased in work efficiency or productivity [7][8][9][10][11]. Sure, this does not signify that workers must only passively accept the condition.…”
Section: Purnawati Et Almentioning
confidence: 99%